Succession of splicing regulatory elements determines cryptic 5΄ss functionality - Brillen, Anna-Lena (Nucleic Acids Res, 2017)
A critical step in exon definition is the recognition of a proper splice donor (5΄ss) by the 5’ end of U1 snRNA. In the selection of appropriate 5΄ss, cis-acting splicing regulatory elements (SREs) are indispensable. As a model for 5΄ss recognition, we investigated cryptic 5΄ss selection within the human fibrinogen Bβ-chain gene (FGB) exon 7, where we identified several exonic SREs that simultaneously acted on up- and downstream cryptic 5΄ss. In the FGB exon 7 model system, 5΄ss selection iteratively proceeded along an alternating sequence of U1 snRNA binding sites and interleaved SREs which in principle supported different 3’ exon ends. Like in a relay race, SREs either suppressed a potential 5΄ss and passed the splicing baton on or splicing actually occurred. From RNA-Seq data, we systematically selected 19 genes containing exons with silent U1 snRNA binding sites competing with nearby highly used 5΄ss. Extensive SRE analysis by different algorithms found authentic 5΄ss significantly more supported by SREs than silent U1 snRNA binding sites, indicating that our concept may permit generalization to a model for 5΄ss selection and 3’ exon end definition.